(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Aim of the research: to explore the possibility of building professional competence of physical culture educators in higher education institutions. Methods and organization of the research: theoretical modeling, interpretation, survey and diagnostic methods, expert assessment, observation, pedagogical experiment, mathematical processing of research outcomes. Th e study involved 30 teachers of the Department of physical education and sports and coaching staff in Kazan State University of architecture and civil engineering. At fi rst, we selected the tools and methodology of the study. Secondly, we designed a competency development model for physical culture educators in higher education institutions. Th e third step included experimental research on building professional competence of educators with consideration of the developed model.